2020
DOI: 10.1111/irv.12802
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of SARS‐CoV‐2‐specific IgG detection with a rapid antibody kit for COVID‐19 patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Guo et al reported that the positive rates of IgM antibodies and IgG antibodies in SARS‐CoV‐2‐infected patients increased significantly after 7–14 days of symptoms 8 . Another study reported that the IgG detection rates reached 100.0% in samples collected on day 13 or later using an immunochromatographic assay kit 9 . Considering the uncertainty of the time patients can recall the symptoms, this study used the number of days of admission as the basis for grouping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al reported that the positive rates of IgM antibodies and IgG antibodies in SARS‐CoV‐2‐infected patients increased significantly after 7–14 days of symptoms 8 . Another study reported that the IgG detection rates reached 100.0% in samples collected on day 13 or later using an immunochromatographic assay kit 9 . Considering the uncertainty of the time patients can recall the symptoms, this study used the number of days of admission as the basis for grouping.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study reported that the IgG detection rates reached 100.0% in samples collected on day 13 or later using an immunochromatographic assay kit. 9 Considering the uncertainty of the time patients can recall the symptoms, this study used the number of days of admission as the basis for grouping. The results showed that the positive rates of IgM and IgG antibodies 1-3 days, 4-6 days, 7-9 days and more than 9 days after admission (see Figure 3) were 50%, 70%, 92.5% and 97.5%, respectively, suggesting that the antibody positivity rate increased rapidly during the early stages of infection, and antibody detection can be used as an indicator for SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“… Antigen tests : analysis of the viral proteins (membrane-bound spike proteins or the nucleocapsid proteins) using techniques such as colorimetric, field-effect transistor (FET), enzyme-linked immunosorbent assay (ELISA), and mass spectrometry (MS). Serological tests : analysis of the antibodies (Immunoglobulin M (IgM) and Immunoglobulin G (IgG)) against the virus [ 188 190 ]. The study of patient's antibodies can be achieved using methods such as electrical (EC) biosensors, localized surface plasmon resonance (LSPR), surface-enhanced Raman scattering (SERS), quartz crystal microbalance (QCM), fluorescence-based biosensor, colorimetric biosensor, gold immunochromatography, ELISA, chemiluminescence immunoassay, and piezoelectric microcantilever sensors (PEMS).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, studies clearly demonstrated that the presence of anti-SARS-CoV-2 IgG does not indicate viral clearence. 1,8 Nevertheless, a report by Long et al 4 verified that moderate and severe COVID-19 patients present a distinct IgM and IgG production course. Severe patients develop IgG seroconversion earlier in relation to moderate patients.…”
mentioning
confidence: 99%
“…2 Reports have detected IgG production between 5 and 9 days after infection. 1,3,4 Nevertheless, patients with some comorbidities, such as HIV, can present a delayed immune response against SARS-CoV-2, with detectable anti-SARS-CoV-2 immunoglobulin only after 60 days after the infection. 5 Anti-SARS-CoV-2 IgG may block and neutralize SARS-CoV-2 and prevent COVID-19 development.…”
mentioning
confidence: 99%